Modular synthesis and immunological evaluation of suspected allergenic galactooligosaccharides. Issue 12 (7th March 2019) - Elferink, Hidde; Rossing, Emiel; Huang, Chiung-Hui; Lee, Bee Wah; Cao, Linqiu; Delsing, Dianne J.; Groeneveld, Andre; Boltje, Thomas J.
Abstract : The synthesis of suspected GOS-related allergens using a flexible modular approach and their immunological evaluation are reported. Abstract : Galactooligosaccharides (GOS) are widely used in the food industry as prebiotics and in very rare cases, can lead to an allergic reaction. Due to the microheterogeneity of GOS it is very difficult to extract pure and well defined oligosaccharides to establish which component is responsible for the observed allergenicity. Herein, we report the chemical synthesis of a suspected allergen 4PX and three closely related oligosaccharides based on a modular approach. The fact that synthesized 4PX and a regioisomer did not cause basophil activation in subjects with confirmed GOS-allergy excludes both tetrasaccharides as key-epitopes in GOS-allergenicity in Singapore.